Colour, Magnets and Photosynthesis. Issue 1 (February 2015) - O'Brien, Frances; Herbert, Sandra
THIS STUDY INVESTIGATED THE teaching and learning approaches of three Victorian early childhood kindergarten teachers to science education, and how they used the Victorian Early Years Learning and Development Framework (VEYLDF) to support them in the development of science in their curriculum. A qualitative, collective case study was designed to investigate how the participants introduced and explored science in their curriculum through two face-to-face individual, semi-structured interviews, separated by a week during which they completed a reflective journal focusing on science in their curriculum. The findings revealed teachers' own negative school experiences of science education and an overall lack of confidence in their current science knowledge impacts on science in their curriculum. Conversely the findings also revealed instances of science learning and discovery, as well as a desire by the early childhood teachers to enhance science education in their curriculum.